By the Honourable John Nanfan, Esq ; His Majesties lieut. governour and commander in chief in and over the province of New-York ... A proclamation : Whereas Coll. Nicholas Bayard and Alderman John Hutchins, together with some few other persons, disaffected to this His Majesties government ... have incited the people to disown the present authority ... Given at Fort William Henry in New-York, this 24th day of January, 1701 . (Printed by William Bradford, printer to the Kings most excellent Majesty, 1701)
Requesting that riots be put down and peace be restored to the counties of New York.